Shotgun proteomics profiling of chia seeds (Salvia hispanica L.) reveals genotypic differential responses to viability loss - Rodríguez, María Emilia (2024)
Introduction: Exposure to elevated temperatures and relative humidity expeditesthe seed aging process, finally leading to seed viability loss. In this context, certainproteins play a pivotal role in safeguarding the longevity of seeds. However, theseedproteomic response to loss viability in Salvia hispanica L., commonly knownas chia, remains incompletely understood.Methods: This work explores the application of proteomics as a potent tool foruncovering molecular responses to viability loss caused by artificial aging in twochia genotypes, WN and MN.Results: By using a quantitative label-free proteomics analysis (LC-MS/MS), 1787proteins wereidentified in chia seeds at a 95% confidence level, including storageproteins, heat shock proteins (HSPs), late embryogenesis abundant proteins (LEA),oleosins, reactive oxygen species (ROS)-related enzymes, and ribosomal proteins.A relatively low percentage of exclusive proteins were identified in viable and nonviable seeds. However, proteins exhibiting differential abundancebetween samplesindicated variations in the genotype and physiological status. Specifically, the WNgenotype showed 130 proteins with differential abundancecomparing viable andnon-viable seeds, while MN displayed changes in the abundance of 174 proteins.While both showed a significant decrease in keyproteins responsible formaintaining seed functionality, longevity, and vigor withhigh-temperature andhumidity conditions, such as LEA proteins or HSPs, ROS, and oleosins, distinctresponses between genotypes were noted, particularly in ribosomal proteins thatwere accumulated in MN and diminished in WN seeds.Discussion: Overall, the results emphasize the importance of evaluating changesin proteins of viable and non-viable seeds as they offer valuable insights into theunderlying biological mechanisms responsible for the maintenance of chia seedintegrity throughout high-temperature and humidity exposure.